STUDI PREFERENSI PENGGUNAAN BENIH PADI DI JAWA TENGAH - Sularno Sularno; Agus Sutanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2003)
Study of preference on rice seed use at farmer level was carried out in Central Java. Data were collected through interviewing using structured questionnaries with 320 respondents in eight Regencies of Grobogan, Sragen, Sukoharjo, Klaten, Boyolali, Semarang, Temanggung and Batang, from April to August 2002. Information and data gained were consisted of a primary and secondary data related to rice seed demand. Data were analyzed by descriptive and explanation methods to seek the relationship between rice seed preference and indicator measured. The result revealed that farmers generally tend to choose rice seed with characteristic of high yielding; better taste and resistance. to pest and disease. In relation to factor affecting the use rice seed, the education attainment of farmers in Regencies of Boyolali, Semarang and Batang was identified to be intluence on the rice seed choice. Meanwhile, it had no relationship with the choice of rice seed in other five regencies.